A synergistic combination of nutrient reclamation from manure and resultant hydrochar upgradation by acid-supported hydrothermal carbonization. (November 2017) - Dai, Lichun; Yang, Bo; Li, Hong; Tan, Furong; Zhu, Nengmin; Zhu, Qili; He, Mingxiong; Ran, Yi; Hu, Guoquan
Graphical abstract: Highlights: Cattle manure was hydrothermally carbonized in dilute acid (0–2% HCl). HTC with acid addition increased nutrient extraction remarkably. HTC with acid addition extracted much more nutrients as NH4 -N and PO4 -P. HTC with acid addition remarkably improved resulting hydrochar properties. Abstract: Cattle manure was hydrothermally carbonized in acid solutions (0–2% HCl), then nutrient concentration in liquid product and physicochemical properties of hydrochar were characterized to investigate the effects of acid addition on hydrochar properties and nutrient recovery from manure. Results showed that hydrothermal carbonization (HTC) in 2% HCl extracted almost 100% and 63.38% of phosphorus and nitrogen, respectively; specifically, >90% of the extracted phosphorus was PO4 -P in liquid from HTC with acid addition, and increasing amount of extracted nitrogen was NH4 -N with increasing acid addition. Generally, higher heating value, surface area, total pore volume, fixed carbon, atomic ratios of H/C and O/C were increased in hydrochars from HTC with acid addition, while yield, volatile matter, contents of nitrogen, sulfur and oxygen of these hydrochars were decreased. These results indicated that HTC with acid addition could simultaneously facilitate nutrient recovery from manure and resulting hydrochar upgradation.